Evaluation of the Financial Performance of Indonesian Sharia Banks Pre and Post Merger - Sidik, Jihad Sabililah; Adnan, Muhammad Akhyar; Gunawan, Andri (Research of Islamic Economics, 2026)
This research is motivated by the merger of three Islamic banks, namely Bank BNI Syariah, Bank BRI Syariah, and Bank Syariah Mandiri, into Bank Syariah Indonesia based on several ratios in SEOJK Number 10/SEOJK.03/2020 and the merger approval stated in the Decree of the Board of Commissioners of the Financial Services Authority Number 4/KDK.03/2021. The purpose of this study is to analyze the financial performance before and after the merger using financial ratios prescribed by the Financial Services Authority, with the expectation that the results will serve as a reference for evaluating the success of Bank Syariah Indonesia in implementing the merger. This study applies a comparative method using secondary data obtained from the annual financial statements of the three predecessor banks for 2019–2020 and the quarterly financial statements of Bank Syariah Indonesia for 2021–2022. The findings show that ROA, ROE, BOPO, and NOM improved after the merger, while CKPN, NI, and Profit-Sharing Financing to Total Financing recorded less favorable outcomes. The managerial implications highlight the importance of maintaining operational efficiency, optimizing assets, and improving post-merger integration. Management is also encouraged to reinforce credit risk controls and improve revenue structures to ensure long-term financial stability.